Automation and Robotics - Boboulos, Miltiadis A. (BookBoon, 2012)
In this book for the optimization of assembly conveyor lines we are dealing with series part production featured by a medium complexity degree and a medium number of individual components and assembly technique alternatives. Modern production techniques for medium to large series products or mass production usually involve assembly conveyor lines.